Poster Media Program Promosi Kesehatan Pencegahan Dismenore dengan Pola Makan Anti Inflamasi Berbasis Penyembuhan Melalui Nutrisi (Lembaga Pengembangan Kinerja Dosen, 2026)
Adolescent reproductive health is an important aspect that requires special attention, especially regarding the problem of dysmenorrhea or menstrual pain. Dysmenorrhea is often considered normal, even though it can reduce the quality of life and disrupt the learning activities of young women. One factor that influences dysmenorrhea is nutritional status and diet. This community service activity aims to increase the knowledge of young women about preventing dysmenorrhea through health promotion using posters with an anti-inflammatory diet approach based on